Capillary filling, evaporation and condensation in nanochannels - Nguyen, Phan Vinh (2012)
The recent advances in fabrication of nanoscale structures allow in-depth investigation of transport effects in nanochannels. This thesis presents the theoretical and experimental investigations of capillary filling, gas absorption in liquid, evaporation and condensation in nanochannels. To prepare for the experiments, nanochannels were fabricated in silicon and polymer. Silicon nanochannels were fabricated by reactive ion etching and anodic bonding methods while polymeric planar nanochannels were fabricated by hot embossing and thermal bonding. The discrepancy between theoretical and experimental results in capillary filling suggests that electroviscous effect is not the only cause of the reduction in filling speed in nanochannels. The experiments on capillary filling in closed-end silicon nanochannels show that the meniscus continues to fill until the end of the nanochannel. Classical theory cannot explain this phenomenon. A novel mathematical model which considers the gas absorption and diffusion fits the experimental data well. Experimental results on drying of ethanol in nanochannels agree well with the theoretical model based on diffusion. In addition, the condensation of liquid in nanochannels was observed when a stream of evaporated vapour was blown across the entrance of the nanochannels.